Legal Evolution of Same-Sex Marriage in Ireland - Agnieszka Targońska (Studia Iuridica Lublinensia, 2022)
The legalization of same-sex relationships has always been a controversial subject. Ireland is a good example of such a case, which decided to legalize same-sex marriages following a referendum held in 2015. Conclusions which stem from the Irish experience in this matter can provide valuable lessons for those countries that have not yet legalized one-sex marriages. The subject of this article is an analysis of the path that Ireland has undertaken to legalize same-sex marriages and an indication of current Irish regulations concerning these marriages. The aim is to discuss legal evolution of the institution of same-sex marriages in Ireland and its consequences for the constitutional order and social perception of the Irish citizens. Due to the fact that there is a lack of complex legal research of this subject in Poland, this article constitutes a gap-filling study. The article has a scientific and research character and may constitute a contribution to further legal considerations on the issue of same-sex marriages in the EU states.